Endogenous Security for the Space-Integrated-Ground Information Network in 6G - Xinsheng JI; Kaizhi HUANG; Jiangxing WU; Yajun CHEN; Wei YOU (天地一体化信息网络)
The space-integrated-ground information network in 6G is facing security challenges due to its characteristics, such as the high exposure of the network, high-speed movement of nodes, limited computing resources.Moreover, new security issues are certainly introduced in the development of new architectures, new applications, new technologies and so on.It is urgent to propose new universal security theories to overcome safety and security threats by the integrated solutions.For this purpose, this paper first expounded the cyberspace endogenous security and proposed its endogenous security architecture.Then, under the guidance of the cyberspace endogenous security theory, the relevant security theory and practice norms were respectively discussed for onboard systems, 6G ground mobile networks, and satellite-ground links.Finally, the authentication and encryption mechanism of the communication and security integration from the aspects of security authentication and high security communication encryption, and the integration of traditional security technology and endogenous security were analyzed.